Acinetobacter baumannii: Polymyxins Bind to the Cell Surface of Unculturable Acinetobacter baumannii and Cause Unique Dependent Resistance (Adv. Sci. 15/2020). Issue 15 (5th August 2020) - Zhu, Yan; Lu, Jing; Han, Mei‐Ling; Jiang, Xukai; Azad, Mohammad A. K.; Patil, Nitin A.; Lin, Yu‐Wei; Zhao, Jinxin; Hu, Yang; Yu, Heidi H.; Chen, Ke; Boyce, John D.; et al.
Abstract : In article number 2000704, Jian Li and co‐workers elucidate the novel mechanism of dependent resistance to the last‐line polymyxins in a high‐priority "superbug" Acinetobacter baumannii . Polymyxindependent resistance cannot be detected by conventional microbiological diagnosis due to the lack of growth on normal agar plates. These polymyxin‐dependent Acinetobacter baumannii isolates utilize the rigid polymyxin molecules as sticking plasters to stabilize their fragile lipopolysaccharide‐deficient and phosphatidylglycerol‐rich outer membrane.